Silver Nanoparticle Controlled Synthesis and Implications in Spectroscopy, Biomedical and Optoelectronics Applications - Stamplecoskie, Kevin (Université d'Ottawa / University of Ottawa, 2013)
This thesis describes the photochemical synthesis of silver nano particles, several ways to make these particles as well as control the size and shape of the colloidal particles. Understanding the primary reactions in photochemical nanoparticle formation has lead to important contributions to the overall mechanism of metal nanoparticle synthesis. The size and shape control of the particles is shown to have important implications for the Raman spectrum of surface bound molecules. The particles have also been used in antibacterial properties where it was shown that silver nanoparticles are more antibacterial than the corresponding silver cation, while remaining non-toxic to several common cell lines. The particles were also shown to have some interesting properties that can be exploited in lithography and optoelectronics.
Keywords: Photochemistry; Silver Nanoparticles; Plasmon Absorption